Tumour boards in geriatric oncology - Wildes, Tanya Marya; O'Donovan, Anita; Colloca, Giuseppe Ferdinando; Cheung, Kwok-Leung (Oxford University Press, 2018)
Multidisciplinary tumour board (MDT) is an integral part of cancer treatment planning. Although no definite survival benefits have yet been shown by mostly observational studies, other benefits of MDT have been identified. Traditionally the MDT involves participation of treating clinicians – medical, radiation and surgical oncologists. They tend to focus on the cancer alone. There is an increasing awareness that the treatment goal for cancer in older adults is not primarily on prolonging survival, with functional preservation and quality of life being particularly important for this population. The use of comprehensive geriatric assessment and the input of the geriatrician in informing the oncologists regarding treatment decision have increasingly been shown to be beneficial. The integration of the geriatrician into an MDT should be urgently explored.